Cover Crop Management Effects on Soil Water Content and Winter Wheat Yield in Dryland Systems - A. K. Obour; J. D. Holman; J. R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2019)
Integrating cover crop (CCs) into dryland crop production in the semiarid central Great Plains (CGP) can provide several ecosystem benefits. However, CC adoption is slow and not widely popular in the CGP because CCs utilize water that otherwise would be available for the subsequent cash crop. Grazing or haying CCs can provide economic benefits to offset revenue loss associated with decreased crop yields when CCs are grown ahead of a cash crop. Objectives of the current research were to 1) determine forage production of CC mixtures, and 2) evaluate the impacts of removing CC for forage on soil water content, subsequent crop yields, and soil health. Cover crop treatments evaluated were single, two-, three-, and six-species mixtures of oat, triticale, peas, radish, turnips, and buckwheat compared to chem-fallow. The study was conducted in a wheat-sorghum-fallow rotation system with all crop phases present in each block and year of the study. Results showed that decreasing the proportion of grass species in a CC mixture tended to reduce the amount of forage dry matter (DM) produced. Across the 3 years, forage DM production ranged from 3000 lb/a for the 2-way oat/triticale mixture to 2200 lb/a for the 6-species mixture. However, forage crude protein concentration and digestibility were greatest when peas were included in the mixture. Growing a CC in place of chem-fallow reduced soil water content at winter wheat planting in 2 of the 3 study years. Averaged across years, growing CC ahead of wheat reduced winter wheat yields compared chem-fallow, ranging from 3 bu/a less with spring peas to 13 bu/a when oat CC was hayed. Over the 3-year study, wheat yields with haying or grazing a CC were similar to yields when CC was left as cover. Cover crop treatments had no effect on grain sorghum yields.
Keywords: cover crops; dryland; soil water